Income inequality, entrepreneur formation, and the economic development: evidence from China. Issue 3 (2nd July 2016) - Fan, Zhaobin; Zhang, Ruohan; Liu, Xiaotong
ABSTRACT: On the basis of the role of entrepreneurs in the process of economic development, this paper builds an overlapping generation model to examine the impact of income inequality on economic development from the viewpoint of entrepreneur formation. The results show that in the presence of credit constraints, the impact of income inequality on economic development depends on the stages of development. In the early stages of development, income inequality is beneficial for the formation of entrepreneurs through alleviating the credit constraints. In the later stages of development, however, it is income equality which stimulates the formation of entrepreneurs through alleviating the credit constraints. By the data of China's provinces over the period 2003–2012, this paper estimates the impact of income inequality on the formation of entrepreneurs using the system Generalized Method of Moments approach. The results show that income inequality has a significantly negative impact on the formation of entrepreneurs in both one-step and two-step regressions.